2020
DOI: 10.1002/joc.6956
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclic variability in Pacific decadal oscillation on winter wheat production in China

Abstract: Due to restrictions on the long period ranges of Pacific decadal oscillation (PDO) and the limited amount of winter wheat yield data in China, there is little knowledge or understanding of the effects of PDO on winter wheat production in China. To fill this knowledge gap, we simulated over 100 years of winter wheat yields using a process‐based crop model over eight locations in the dominant winter wheat‐producing area across China during 1902–2014. By using the continuous wavelet transform, we found that winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Soil characteristics of the 3H Plain, predominantly sandy-loam with medium depth, neutral pH, and low-tomoderate levels of organic carbon, were informed by prior research [54,55]. The planting density was set at 200 plants/m 2 , referring to the studies [23,56]. All simulations proceeded under conditions devoid of nitrogen application and reliant on rainfall.…”
Section: Crop Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil characteristics of the 3H Plain, predominantly sandy-loam with medium depth, neutral pH, and low-tomoderate levels of organic carbon, were informed by prior research [54,55]. The planting density was set at 200 plants/m 2 , referring to the studies [23,56]. All simulations proceeded under conditions devoid of nitrogen application and reliant on rainfall.…”
Section: Crop Simulationmentioning
confidence: 99%
“…For example, the impacts of planning date shifts on the phenology of double cropping rice was determined by changing the planning date in the DSSAT CERES-Wheat model [22]. Xu et al [23] analyze the effects of Pacific decadal oscillation (PDO) on winter wheat yields by using the DSSAT CERES-Wheat model and found that when PDO was in the positive (negative) phase, winter wheat yields tended to increase (decrease).…”
Section: Introductionmentioning
confidence: 99%
“…Winter wheat is one of most important staple food crops worldwide, and China is the world's largest wheat producer and consumer [6]. Therefore, there are a large number of papers focusing on the effects of climate change on winter wheat yields in China [7]. Climatic variations are significantly impacted by large-scale oceanic and atmospheric circulation, and several studies have focused on the teleconnections between circulation patterns and wheat yields.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Shuai et al (2013) [8] pointed out that the El Niño-Southern Oscillation (ENSO) has significant impacts on wheat yields, and more rainfall in El Niño years leads to a decrease in wheat yields in the provinces of the Yangtze River basin. Xu et al (2020) [7] indicated that the inter-decadal variations in winter wheat yields in major growing regions of China were significantly associated with the Pacific decadal oscillation (PDO), with its contribution rate to yields being approximately 11%. Chen et al (2020) [9] found that several circulation indices, including PDO, ENSO, SOI, and NAO, had significant impacts on the inter-annual fluctuations of wheat yields in different cities of northern China.…”
Section: Introductionmentioning
confidence: 99%